PENDAMPINGAN SELF-IMAGERY BODY IDEAL MELALUI COUNSELING FITNESS (COUNSFIT ) PADA KOMUNITAS PEDULI ANAK AUTIS LAMPUNG (KOPALA) - Pranoto, Hadi; Al Um Aniswatun Khasanah; Sangidatus Sholiha (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
The method is adapted to meet the needs of children with autism, who often experience body dysmorphia, motor limitations, and a lack of understanding regarding their own body perception. The approach is implemented gradually through physical counseling activities based on motor games, visualization of the ideal body using imagery techniques, and social engagement in community activities. The results show that 80% of participants experienced improvements in physical self-awareness and self-confidence. This program is expected to serve as an alternative integrative intervention that holistically supports the mental and physical health of children with autism.